Pengaruh Harga Diri dan Iri Hati terhadap Kecenderungan Narsistik pada Mahasiswa BK UIN SMDD Bukittinggi Budaya Digital pada Santri - Sri Ratna Juwita; Yeni Afrida (Lembaga Yasin AlSys, 2026)
Narcissistic tendencies among university students have become a psychological issue receiving increasing attention because they are associated with the development of self-concept, the need for social recognition, and the tendency to engage in social comparison. Although the relationships between self-esteem and envy and narcissistic behavior have been examined in various studies, research investigating the simultaneous effects of these two variables among students in the Guidance and Counseling Study Program remains limited. This study aimed to analyze the effects of self-esteem and envy on narcissistic tendencies among students in the Guidance and Counseling Study Program at UIN Sjech M. Djamil Djambek Bukittinggi. The study employed a quantitative approach with a cross-sectional correlational survey design and involved 160 students selected through stratified random sampling. Data were collected using psychological scale questionnaires measuring self-esteem, envy, and narcissistic tendencies. The data were analyzed using descriptive statistics, classical assumption tests, simple linear regression, and multiple linear regression. The results showed that students’ narcissistic tendencies and envy were in the high category, whereas their self-esteem was in the moderate category. The analysis indicated that self-esteem and envy were factors associated with students’ narcissistic tendencies. These findings contribute to the development of self-esteem, self-regulation, and social comparison perspectives in explaining narcissistic tendencies among university students. In practical terms, the results can serve as a basis for higher education institutions and Guidance and Counseling services to design self-development programs, strengthen self-esteem, and improve students’ management of emotions and social relationships. Future research should involve a broader population and consider other psychological variables to obtain a more comprehensive understanding of narcissistic tendencies among university students.